STEREOTYPE OF MADURESE ETHNIC PEOPLE MADE BY JAVANESE ETHNIC PEOPLE THROUGH HUMORS - Tabrani, Akhmad Tabrani; Mbete, Aron Meko; Suastika, I Made Suastika; Mariyah, Emiliana Mariyah (E-Journal of Cultural Studies, 2015)
This study was inspired by several things such as (1) there was a negative impression on the Madurese ethnic people’s attitude and behavior, (2) the conflict taking place between the Madurese ethnic people and the other ethnic groups which resulted from the wrong impression on the Madurese ethnic people, (3) there was a close contact between the attitude and behavior of the Madurese ethnic people and the attitude and behavior of the other ethnic peoples outside Madura. This present study was intended to identify the form, factor, and impact of the stereotype of the Madurese ethnic people made by the Javanese ethnic people through humors. The data in the present study were collected through in-depth interview, observation, documentary study, and library research. There were several factors which contributed to the stereotype of the Madurese ethnic people made by the Javanese ethnic people through humors such as (a) education, (b) legitimacy of violence, (c) ideology, (d) the resistance of the Madurese ethnic people to the Javanese ethnic people, and (e) the Madurese people’s attitude and behavior. The stereotype on the Madurese ethnic people was created to give an inaccurate image although to some extent it was true. The ethnical humor leads to ethnical stereotype. The ethnical humor, which, in this case, was created by the dominant ethnic people, which, in this case, the Javanese ethnic people, contained satire, dislike, hatred, insulting, praise, and resistance of the Madurese ethnic people to the Javanese ethnic people.